Formação de par iônico como uma possível estratégia de aumento da permeação cutanea da paromomicina - Isabel Ramadas Leite Nogueira (2008)
Paromomycin (PA), an aminoglicoside antibiotic, has been used as an alternative for topical treatment of the cutaneous leishmaniasis (CL). Although this treatment has shown promising results, it has not been successful in accelerating the recovery in most cases. This could be attributed, at least in part, to the low skin penetration of PA due to its hidrophilicity. An alternative to increase its skin permeation / penetrationwould be the formation of a neutral ion pair, formed by PA in free base form and organic acids, since lipophilicity of the ionic pair is higher than that of ions individually. This work aimed to synthesise and characterize the following PA salts (ion pairs): lactate, butyrate, benzoate and cinnamate. The impact of the formation of ion pairs on the PA partition coefficient octanol / water (log K), on the PA solubility in solvents of different polarities and on the in vitro skin permeation / penetration of PA,was evaluated. Permeation experiments using pig ear skin were performed in Franz diffusion cells. Two models of skin were used: intact and stripped skin. The formation of ion pairs was insufficient to increase the log K, but increased the solubility of salts in less polar solvents, showing that there was an increase in lipophilicity of the molecules, but insufficient to increase the values of log K. The permeation of the PAfree base and ion pairs across intact skin was low. However, there was increased skin penetration when PA was in the form of ionic pair with lactate and benzoate. In the absence of the SC, there was no increase in the permeation of salts on the PA free base. Although, when the individual salt was compared with PA free base form, it is observed that the amount of PA butyrate and PA cinnamate that permeated through the stripped skin was higher. The salts that showed higher permeation onstripped skin (PA butyrate and PA cinnamate) were those whose penetration into the intact skin was lower. Data obtained in this study suggest that the choice of counterion that will effectively promote the permeation / penetration of the PA must be based on the fact that increasing the molecular weight of counter ion be a limiting factor.